Respuesta :

Answer:

C.2

Step-by-step explanation:

y=2x^-3x+1

Factor

We know that our only choices are 1*1 and -1*-1 to get 1

We need to get a sum of -3  so I will pick -1 and -1

(2x-1) (x-1)

Check

FOIL

2x^2 -2x-x+1 = 2x^-3x+1

y = (2x-1) (x-1)

0 =(2x-1) (x-1)

Using the zero product property we can find where it crosses the x axis

0 =(2x-1)         0 =(x-1)

2x-1+1 = 0+1          0+1 = x-1+1

2x= 1                          1=x

x = 1/2                        x=1

There are 2 solutions

ACCESS MORE